Análise do efeito do patrimônio líquido no apreçamento de funtos de investimento em ações - Sylvestre, Gustavo Zech (2009)
This article accounts for real returns on a panel of 75 Brazilian stock mutual funds over the last eleven years using the Capital Asset Pricing Model (CAPM) in its canonical version and with non-linear extensions. The results suggest that the traditional and linear CAPM version is not able to price or forecast mutual funds with higher total assets and outperform regarding Brazilian market index (Ibovespa), confirming Matos and Rocha (2009) conclusion. The CAPM model allowing for threshold effects based on total assets seems to deal well with the Jensen-alpha issue, but it is statistically relevant only for funds with high total assets and low outperform values. This finding emphasizes the importance in modeling these assets category using specific risk factors as in Matos and Silva (2009).